Sintesis Turunan Diarilpentanoid dari Sinamaldehida - Lerrick, Reinner Ishaq; Sanit, Karolina T.; Gauru, Imanuel (Chemistry Notes, 2022)
Synthesis of 1,5-Diphenylpenta-2,4-dien-1-one from local cinnamaldehyde has been done. Through aldol condensation reaction submission of local cinnamaldehyde with acetophenone in the presence of KOH resulted in 57% yellow oil confirmed as the desired product by GMMS analysis.